The Influence of Green Self-Efficacy, Employee Engagement, Organizational Commitment, and Work-Life Balance on Sustainable Job Satisfaction with Green Organizational Culture as a Mediating Variable at ADR Group of Companies - Heni Nur Fataya; Agus Arijanto (Indonesian Journal of Business Analytics, 2025)
Amid the dynamics of globalization and the intensifying competition across various business sectors, sustainable job satisfaction has become a fundamental determinant of organizational success. Furthermore, Green Organizational Culture is considered a mediating factor in the relationship between Green Self-Efficacy, Employee Engagement, and Organizational Commitment with Sustainable Job Satisfaction. This study employed a quantitative approach using the Two Stage Approach. Data were collected from 334 employees of ADR Group of Companies, selected from a total population of 2,000 using the Slovin formula with a 5% margin of error and simple stratified random sampling techniques.  The results showed that Green Self-Efficacy has a positive and significant effect on both Sustainable Job Satisfaction and Employee Engagement. Employee Engagement was also found to have a positive and significant impact on Sustainable Job Satisfaction. Green Organizational Culture demonstrated a positive and significant relationship with Sustainable Job Satisfaction.  The study also highlighted the mediating role of Employee Engagement and Green Organizational Culture. Employee Engagement positively and significantly mediated the effect between Green Self-Efficacy and Sustainable Job Satisfaction. However, Green Organizational Culture did not mediate the effect of Green Self- Efficacy and Employee Engagement on Sustainable Job Satisfaction.